2013
DOI: 10.1016/j.icarus.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of spokes in Saturn’s B ring

Abstract: We present the first results from Cassini ISS observations aimed at determining both the short-term and long-term behavior of the spokes in Saturn's B ring.We have observed multiple spokes which appear between images where there was not a spoke before. The radial termini of these new spokes expand radially at ∼ 0.5 km/s in both the inward and outward directions and both towards and away from corotation. Defining a spoke's activity as the area-integrated optical depth over the region of the ring it covers, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…With regard to ring region phenomena, however, it has been reported that two types of disturbances in Saturn's rings exhibit periodicities which appear to be related to the PPOs. First, it has been found by Porco and Danielson (1982) and Mitchell et al (2013) that the occurrence of ring "spokes" appearing in the B ring near synchronous orbit is modulated at periods comparable with the PPO periods. Second, Hedman et al (2009) and Chancia et al (2019) have reported the presence of patterns in the tenuous material in Saturn's D ring and Roche division (between the A ring and the outer F ring) which rotate with periods near the concurrent dominant PPO period.…”
Section: Ppos and Mean Fields On Ring Region Field Linesmentioning
confidence: 99%
“…With regard to ring region phenomena, however, it has been reported that two types of disturbances in Saturn's rings exhibit periodicities which appear to be related to the PPOs. First, it has been found by Porco and Danielson (1982) and Mitchell et al (2013) that the occurrence of ring "spokes" appearing in the B ring near synchronous orbit is modulated at periods comparable with the PPO periods. Second, Hedman et al (2009) and Chancia et al (2019) have reported the presence of patterns in the tenuous material in Saturn's D ring and Roche division (between the A ring and the outer F ring) which rotate with periods near the concurrent dominant PPO period.…”
Section: Ppos and Mean Fields On Ring Region Field Linesmentioning
confidence: 99%
“…Indeed, there are several patterns in both the D ring and Roche Division which appear to be generated by resonances with multiple periodic perturbations with effective pattern speeds around 800 • /day and 820 • /day (Hedman et al 2009), and these may correspond to the 2:1 and 3:4 tesseral resonances, respectively. In addition, the dusty spokes that form close to the planetary co-rotation radius also exhibit periodicities that have been tied to Saturn's rotation rate (Porco & Danielson 1982;Porco 1983;Mitchell et al 2013). However, all of these previously-studied structures involve ring material composed primarily of micron-sized particles.…”
Section: Multiple M = +3 Waves In the Outer C Ringmentioning
confidence: 99%
“…Energetic neutral atoms, generated by collisions between neutrals and charged particles, also display periodic behavior that can be observed on a global scale (Carbary, Mitchell, Brandt, Roelof, et al, ; Paranicas et al, ). Even spokes in Saturn's rings appear to show a periodic behavior (Mitchell et al, ; Porco & Danielson, ).…”
Section: Introductionmentioning
confidence: 99%